The Haunted - Vega, Danielle (New York : Razorbill, an imprint of Penguin Random House LLC, 2019)
To evade her manipulative ex-boyfriend, sixteen-year-old Hendricks family moves to small-town New York, where she joins the popular crowd, but only her outcast neighbor, Eddie, can help chase vindictive ghosts from her new house.
Keywords: Haunted houses -- Fiction; Moving, Household -- Fiction; Friendship -- Fiction; Dating (Social customs) -- Fiction; Families -- New York (State); Fiction; New York (State) -- Fiction